FIRST FIND OF BISMUTH GEVERSITE PT(BI, SB)21 - Ponomarenko A.I.; Malov V.S. (My University, 1990)
The first find of a new variety of the intermetallic platinum compound Pt(Bi, Sb)2, belonging to the geversite (PtSb2)-insizwaite (PtBi2) solid solution series, was made in the Talnakh Deposit, at the Oktyabrskiy Mine. The mineral is brittle, with indistinct cleavage and a hardness of 660 kg/mm2 under a load of 0.02 to 0.05 kg. It takes a high polish. In reflected light, the mineral is white, without perceptible birefringence, and is isotropic under crossed Nicols.